Redefining the Genus Corollospora Based on Morphological and Phylogenetic Approaches - Pedro Correia; Egídia Azevedo; Maria F. Caeiro (Journal of Fungi, 2023)
The present study, initially to resolve the cryptic species within Corollospora maritima, is to determine how to attain taxonomic discrimination at species and generic levels. Multiple sequence alignments (MSAs) of the ITS, 28S, and 18S regions of the nuclear ribosomal cistron were separately subjected to pairwise distance assessments, Bayesian, and Maximum likelihood phylogenetic analyses. Morphological descriptions of 15 type strains of Corollospora species, along with MSAs involving representatives of the whole genus Corollospora (268 isolates, many from C. maritima sensu lato) totaling 355 published sequences, allowed phylogenetic assessments conducted to the following p-distance thresholds in the ITS/28S regions: ≥3%/1% for species segregation and ≥8%/2% for generic segregation. This resulted in the introduction of 10 new genera encompassing 13 new combinations of current Corollospora species: Ajigaurospora pseudopulchella, Corollosporella anglusa, Corollosporella ramulosa, Corollosporopsis portsaidica, Garethelia parvula, Honshuriella fusca, Keraliethelia pulcehlla, Nakagariella filiformis, Paracorollospora angusta, Paracorollospora luteola, Paracorollospora marina, Shirahamella gracilis, and Tokuratelia colossa. Furthermore, seven undefined genera considered putative new genera (pNGenus A to G), and 16 undefined putative new species (seven spp. come from the resolution of the C. maritima complex), await re-assessment of their morphology and additional molecular data, which may result in the recognition of new taxa.